2021
DOI: 10.1177/00220221211032393
|View full text |Cite
|
Sign up to set email alerts
|

Virtue, Shame, and Choice: Perspectives of Sex Work Among Adolescents in Variously Globalized Thai Communities

Abstract: Although taboo given the traditional Thai value of female sexual conservatism, sex work is a practice for which Thailand has gained international attention. As in other rapidly globalizing contexts, however, Thai youth are increasingly exposed to global values of gender equality, self-fulfillment, and personal choice. This may, in turn, alter youth perspectives of this taboo yet pervasive practice. To understand how Thai youth negotiate local and global values when considering sex work, this study examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…As the tourism demand has increased rapidly and boosted the growth of Thailand’s tourism industry, many poor transgender women and gay men have moved and worked in the sex industry as their only feasible option (Davis et al, 2019 ; Ocha, 2020 ; Statham & Scuzzarello, 2021 ). Despite being illegal, the sex industry in Thailand employs about 200,000 to more than 1 million sex workers (Amendral, 2021, as cited in McKenzie et al, 2021 ), which is undoubtedly regarded to be a significant underestimation. Thailand’s GDP amounted to 401.27 billion US dollars in 2015 (Statista, 2022 ) and the Havocscope’s research report ( 2015 ) showed that the sex industry generated 6.4 billion US dollars in 2015, accounting for almost 1.6% of Thailand’s total GDP.…”
Section: Introductionmentioning
confidence: 99%
“…As the tourism demand has increased rapidly and boosted the growth of Thailand’s tourism industry, many poor transgender women and gay men have moved and worked in the sex industry as their only feasible option (Davis et al, 2019 ; Ocha, 2020 ; Statham & Scuzzarello, 2021 ). Despite being illegal, the sex industry in Thailand employs about 200,000 to more than 1 million sex workers (Amendral, 2021, as cited in McKenzie et al, 2021 ), which is undoubtedly regarded to be a significant underestimation. Thailand’s GDP amounted to 401.27 billion US dollars in 2015 (Statista, 2022 ) and the Havocscope’s research report ( 2015 ) showed that the sex industry generated 6.4 billion US dollars in 2015, accounting for almost 1.6% of Thailand’s total GDP.…”
Section: Introductionmentioning
confidence: 99%